2022
DOI: 10.1155/2022/6609901
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Characteristic Genes in Whole Blood of Intervertebral Disc Degeneration Patients by Weighted Gene Coexpression Network Analysis (WGCNA)

Abstract: Intervertebral disc degeneration (IDD) is a major cause of lower back pain. However, to date, the molecular mechanism of the IDD remains unclear. Gene expression profiles and clinical traits were downloaded from the Gene Expression Omnibus (GEO) database. Firstly, weighted gene coexpression network analysis (WGCNA) was used to screen IDD-related genes. Moreover, least absolute shrinkage and selection operator (LASSO) logistic regression and support vector machine (SVM) algorithms were used to identify characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 66 publications
(65 reference statements)
0
16
0
Order By: Relevance
“…Circulating RNA molecules could be analyzed to identify novel and promising biomarkers for numerous diseases (Li et al, 2014). Recent studies, using RNA-seq to assay the repertoire of genes within a tissue or cell have identified unique mechanistic pathways in human blood cells of patients with rheumatoid arthritis (Reynolds et al, 2013), IDD (Ma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating RNA molecules could be analyzed to identify novel and promising biomarkers for numerous diseases (Li et al, 2014). Recent studies, using RNA-seq to assay the repertoire of genes within a tissue or cell have identified unique mechanistic pathways in human blood cells of patients with rheumatoid arthritis (Reynolds et al, 2013), IDD (Ma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating RNA molecules could be analyzed to identify novel and promising biomarkers for numerous diseases ( Li et al, 2014 ). Recent studies, using RNA-seq to assay the repertoire of genes within a tissue or cell have identified unique mechanistic pathways in human blood cells of patients with rheumatoid arthritis ( Reynolds et al, 2013 ), IDD ( Ma et al, 2022 ). In conclusion, taking advantage of cutting-edge techniques in RNA-seq analysis, we have unprecedentedly integrated mRNA, lncRNA, circRNA, and miRNA profiles in Normal, LDH, and ADS, analyzed the crosstalk of multiple ncRNAs in the regulation of disc degeneration while focusing on the ncRNAs associated with the pathogenesis of ADS.…”
Section: Discussionmentioning
confidence: 99%
“…It regulates not only inflammation, but also autoimmune diseases (Yeung et al, 2000;Paul et al, 2014). It may play a role in IDD by modulating immune and inflammatory responses (Ma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al . also identified key genes in blood of patients with intervertebral disc degeneration (IDD) as important biomarkers based on LASSO regression analysis [ 29 ]. To screen out key genes correlated with AF, “glmnet” package was used to perform LASSO regression algorithm.…”
Section: Methodsmentioning
confidence: 99%